Moral Attitude dan Eco-commitment Pengusaha UKM Tepung Tapioka terhadap Lingkungan Hidup: Studi kasus di Pati, Jawa Tengah - Anastasia Mutia Wardani; Rooskities Andadari; Widhi Handayani (Graduate School Bogor Agricultural University (SPs IPB), 2022)
The manufacturing industry has an important role on the regional economic’s development. Nevertheless, economics development cannot be separated from environmental degradation issue. In Margoyoso Sub-district, Pati, Central Java, the disposal of tapioca flour wastewater results in environmental pollution and this situation rises a question on the awareness of entrepreneurs. The purpose of this study is to identify the moral attitude of tapioca entrepreneurs to the environment and to explore the efforts made by entrepreneurs to reduce the negative impacts of the wastewater. This research is conducted by qualitative method, using interview, observation, and documentation for data collection. The results of this study indicate that the moral attitude of tapioca entrepreneurs is classified as socionomous. This implies that the awareness of the entrepreneurs is at low level because the tapioca entrepreneurs run their business by following what other entrepreneurs usually do. Finally, the application of an appropriate eco-commitment concept, namely continuance commitment, is required in order to support the objectives of the business in realizing environmental sustainability for their business.